Is game technique suitable for teaching writing and reading? - Suhid, Asmawati; Hassan, Aminuddin; Abdul Mutalib, Lukman; Che Noh, Mohd Aderi (The International Journal of the Humanities, 2009)
Jawi is known to be very important in the Islamic Education system before the colonial period. However, the use of Jawi has not been emphasized in the post colonial period by the Malaysian Ministry of Education as it is not fully used even in the Islamic Education subject. Recently, the use of Jawi has been reviewed by the Malaysian government. This review has been positive towards Jawi leading to several significant actions being taken to keep alive the use of Jawi. One of the most important measures taken is the introduction of j-QAF programme. It is based on the Prime Minister’s initiative which stresses the importance of Jawi in the teaching of religious subjects. Hence, teachers are encouraged to use various techniques in the teaching of Jawi. This is because teaching technique is important to ensure the effectiveness of the teaching- learning process. In this paper, a study was carried out to identify the teachers’ perceptions regarding game technique in the teaching of Jawi writing and reading in the j-QAF programme. A set of questionnaire was used to collect the information needed. The quantitative data was analyzed using Statistics Package for the Social Sciences (SPSS) to obtain descriptive statistics indices. The research findings were duly discussed.